Why Countries Differ in Thin Capitalization Rules: The Role of Financial Development - Mohammed Mardan (Center for Economic Studies and ifo Institute (CESifo), 2015)
In the absence of financial frictions, the purpose of thin capitalization rules is to limit multinational firms' possibilities of engaging in tax planning via debt shifting. This paper analyzes the effects of thin capitalization rules in the case where firms have limited access to external funding. First, we show that a host country allows positive internal interest deductions if its financial development is sufficiently low. This amount increases when the financial development of the host country worsens. Then we ask which of the two most common thin capitalization rules used in practice is better suited to maximizing welfare of the host country. We show that welfare under a safe haven rule is higher than under an earnings stripping rule if firms are not able to manipulate transfer prices. Welfare, however, can be higher under an earnings stripping rule if firms are able to manipulate transfer prices. The analysis provides an explanation for why countries differ in the strictness and in the type of thin capitalization rule.
Keywords: H25; G38; F23; 330; thin capitalization rule; safe haven rule; earnings stripping rule; debt shifting; financial development